TSPAN15 sustains ITGB1 stability to block gemcitabine-induced ferroptosis in pancreatic ductal adenocarcinoma through the FAK/AKT/Mtor-gpx4 cascade - Peng Nan; Xiao Wang; Anan Li; Yumei Ge; Zongting Gu; Yingying Wang; Ran Tao (Redox Biology)
Chemotherapy remains a pivotal strategy in the treatment of pancreatic ductal adenocarcinoma (PDAC). Nonetheless, the emergence of drug resistance has limited the clinical efficacy of chemotherapeutic agents, especially gemcitabine. Here, we identified tetraspanin-15 (TSPAN15), a member of the tetraspanin family, that is frequently overexpressed in human PDAC and is correlated with tumor progression and poor prognosis. Elevated levels of TSPAN15 are involved in mediating gemcitabine resistance of in cancer cells, primarily by inhibiting ferroptosis. Knocking down TSPAN15 increases the sensitivity of PDAC cells to gemcitabine in vitro and in vivo by increasing the susceptibility of cancer cells to ferroptosis. Mechanistically, TSPAN15 directly interacts with integrin-β1 (ITGB1) and maintains its stability by inhibiting ITGB1 ubiquitination. This interaction activates the downstream p-FAK/p-AKT/p-mTOR axis and promotes the expression of glutathione peroxidase 4 (GPX4), a central negative regulator of ferroptosis, ultimately attenuating gemcitabine-induced ferroptosis in PDAC cells. Venetoclax, a newly identified targeted inhibitor of TSPAN15, exhibits synergistic efficacy when combined with gemcitabine for treating PDAC both in vitro and in vivo. This study reveals, for the first time, a major clinically relevant chemoresistance mechanism in PDAC mediated by TSPAN15 in sustaining ITGB1/p-FAK/p-AKT/p-mTOR-GPX4 signaling and tuning ferroptosis, revealing its potential as a viable therapeutic target for chemosensitization.